Holistic Management of Depressive-Type Schizoaffective Disorder: A Case Illustration - Muh Azka Aldani Fadhlurahman; Hafid Algristian; Yekti Mumpuni (Indonesian Scientific Publication, 2026)
Schizoaffective disorder is a complex psychiatric condition characterized by the coexistence of psychotic and mood symptoms, often requiring comprehensive and long-term management. Achieving sustained clinical stability in depressive-type schizoaffective disorder remains challenging, particularly when psychosocial stressors and limited support systems are present. This case illustration describes a holistic management approach integrating pharmacological treatment, structured family involvement, and patient-centered spiritual coping within an Indonesian cultural context. We present the case of a 44-year-old female diagnosed with depressive-type schizoaffective disorder based on the Indonesian Guidelines for the Classification and Diagnosis of Mental Disorders, corresponding to international diagnostic principles. Clinical data were obtained through psychiatric interviews, longitudinal clinical observation, and review of medical records. The intervention consisted of combined antipsychotic and antidepressant pharmacotherapy, accompanied by structured family support and ethically integrated spiritual coping strategies aligned with the patient’s preferences. Over the course of follow-up, the patient demonstrated a reduction in psychotic symptoms (notably ideas of reference) and depressive features, alongside improvements in sleep patterns, self-care, treatment adherence, and emotional regulation. Functional gains were observed in daily activities and engagement with meaningful roles, with no acute relapse reported during the observed follow-up period. Family involvement contributed to adherence monitoring and stress reduction, while spiritual coping functioned as an internal resource for meaning-making and resilience rather than as a standalone intervention. This case illustrates that a holistic management strategy addressing biological, psychosocial, and spiritual dimensions may support clinical stabilization and functional recovery in depressive-type schizoaffective disorder. While findings from a single case cannot be generalized, this report highlights the potential clinical value of integrating family support and patient-centered spirituality into routine psychiatric care within culturally relevant settings.